2017
DOI: 10.1039/c7ra12145h
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun polyacrylonitrile nanofiber mat protected membranes for vanadium flow batteries

Abstract: The cycling stability of the SPEEK membrane in vanadium flow batteries is remarkably improved by using a PAN nanofiber mat as a protection layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…The main electrochemical parameters of EIS analysis at different humidification conditions, obtained by using the Randles equivalent circuit (see the Experimental Section for further details), are summarized in Table 1 . It is worth highlighting that the very low R ct values were similar to those reported for membrane electrode assembly (MEA) in fuel cells, where the Nafion membranes were used as reference SPEs . In this regard, Klingele et al also demonstrated that the direct deposition of the electrodes on the polymer electrolyte membranes further reduced the R ct values in the resulting fuel cell devices .…”
Section: Resultssupporting
confidence: 55%
“…The main electrochemical parameters of EIS analysis at different humidification conditions, obtained by using the Randles equivalent circuit (see the Experimental Section for further details), are summarized in Table 1 . It is worth highlighting that the very low R ct values were similar to those reported for membrane electrode assembly (MEA) in fuel cells, where the Nafion membranes were used as reference SPEs . In this regard, Klingele et al also demonstrated that the direct deposition of the electrodes on the polymer electrolyte membranes further reduced the R ct values in the resulting fuel cell devices .…”
Section: Resultssupporting
confidence: 55%
“…In aV FB, SPEEK is at ypical material with high H + /V selectivity ascribed to its rigid structure, [79] but this also makesS PEEIK prone to degradation, [18] which resultsi nc apacity fading.A n externalp rotection was achievedu sing poly(tetrafluoroethylene) (PTFE), [80] rice paper, [81] or polydopamine(PDA) [39a] to reinforce SPEEK. For instance, inspired by the high stability of PAN, Yu et al [79] reported aP AN/ SPEEK composite membrane (P-S-P) utilizing ar obust protection layer.T he SPEEK support membrane was coveredw ith PANn anofiber,w ith polymers prepared in advance (Figure 7a). The PANn anofiber mat on top of the SPEEK layer protected it from vanadium attack.…”
Section: Composite Membranes In Fb Applicationmentioning
confidence: 99%
“…[39b] Reproduced with permission from Refs. [79] porousP ES-SPEEK substrate to gain ah ighly selectivec omposite membrane for VFBs (Figure 8a). [76] Due to the thin selective Nafion layer (1 mm), the resistance of the composite membrane was comparable with that of Nafion, with proton transport supported by the Grotthuss mechanism; [87] thus, ag ood ionic conductivity was achieved.…”
Section: Composite Membranes In Fb Applicationmentioning
confidence: 99%
See 2 more Smart Citations